Core Binding Factor β (CBFβ) is Retained in the Midbody During Cytokinesis - Lopez-Camacho, Cesar (2014)
Core Binding Factor β (CBFβ) is complexed with the RUNX family of transcription factors in the nucleus to support activation or repression of genes related to bone (RUNX2), hematopoiesis (RUNX1) and gastrointestinal (RUNX3) development. Furthermore, RUNX proteins contribute to the onset and progression of different types of cancer. Although CBFβ localizes to cytoskeletal architecture, its biological role in the cytoplasmic compartment remains to be established. Additionally, the function and localization of CBFβ during the cell cycle are important questions relevant to its biological role. Here we show that CBFβ dynamically distributes in different stages of cell division and importantly is present during telophase at the midbody, a temporal structure important for successful cytokinesis. A functional role for CBFβ localization at the midbody is supported by striking defects in cytokinesis that include polyploidy and abscission failure following siRNA-mediated downregulation of endogenous CBFβ or overexpression of the inv(16) fusion protein CBFβ-SMMHC. Our results suggest that CBFβ retention in the midbody during cytokinesis reflects a novel function that contributes to epigenetic control.